A Psychological Study of Chinese Audience Reception of The Cross-Cultural Film Everything Everywhere All at Once: Why Cultural and Communication Adaptation Fail? - Quan, Rao; Rui, Chen (Mandarinable: Journal of Chinese Studies, 2023)
In most movies, the "imaginary audience" is already hidden in the structure at the beginning of the creation, and the acceptance of the audience means the finalization of the movie art. The overall purpose of this paper is to explore the audience's acceptance of the cross-cultural movie Everything Everywhere All at Once based on cultural adaptation theory and communication adaptation theory. We have to cautiously reflect on whether the ecology of the movie market is undergoing restructuring nowadays, and whether the audience's receptive psychology is changing. Is there a change in the audience's receptive psychology? How can social, psychological, and cultural issues be properly internalized into the core expression of a film? This study collects more than 200,000 words of textual materials from mainstream media channels such as Douban.com, B-station, and Time.com for qualitative research, and utilizes the rooted theory approach to explore the psychological behavioral mechanism of audience's acceptance of cross-cultural films represented by Everything Everywhere All at Once and to construct a theoretical model of the psychology of acceptance in a cross-cultural context. It is found that cultural adaptation and communication adaptation theories have once again emphasized their complex structure and new discourse field in the new cross-cultural movie reception situation. This study expands the applicability of these two theories in the new socio-cultural context of China.